1995
DOI: 10.1021/jm00015a014
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-Size Antagonists of Luteinizing Hormone-Releasing Hormone Active in Vitro

Abstract: A series of reduced-size analogs of LHRH was designed with the length varying from nine to two amino acids. These compounds were tested in vitro for the LH suppression in cultured rat pituitary cells treated with 1 ng of LHRH. The best analogs were also tested in vivo for their antiovulatory activity in rats. It appeared that terminal amino acids as well as the presence of Arg or ILys in the sequence are both crucial for the antagonism. The most potent antagonist in this series was a heptapeptide, AcDNal-Ser-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The reported studies of reduced-size GnRH analogues were traditionaly based on the gradual deletions of residues from either the C- or the N-termini of GnRH or its decapeptide/nonapeptide analogues. There is also a report of a cyclic hexapeptide, a weak GnRH antagonist, which is based solely on the central 5−8 residues . These strategies are not in line with numerous studies which suggested that both termini of the GnRH molecule are involved in direct interactions with the GnRH receptor (for review, see refs and ).…”
Section: Introductionmentioning
confidence: 99%
“…The reported studies of reduced-size GnRH analogues were traditionaly based on the gradual deletions of residues from either the C- or the N-termini of GnRH or its decapeptide/nonapeptide analogues. There is also a report of a cyclic hexapeptide, a weak GnRH antagonist, which is based solely on the central 5−8 residues . These strategies are not in line with numerous studies which suggested that both termini of the GnRH molecule are involved in direct interactions with the GnRH receptor (for review, see refs and ).…”
Section: Introductionmentioning
confidence: 99%
“…Potent GnRH agonists, some of which are already used for clinical purposes, are either decapeptides or nonapeptides (Filicori, 1994). Although thousands of GnRH analogs were synthesized, only very few reports on further reduced-size GnRH analogs were published (Sandow and Konig, 1979;Haviv et al, 1989;Janecka et al, 1995) because deletions of either amino-or carboxyl-terminal amino acids cause a dramatic loss of bioactivity (Karten and Rivier, 1986). A representative example of these small ligands is a hexapeptide corresponding to amino acid residues 4 -9 of the potent GnRH analog buserelin.…”
mentioning
confidence: 99%